IDENTIFIKASI POTENSI EKONOMI DAERAH BOYOLALI, KARANGANYAR, DAN SRAGEN - Titisari, Kartika Hendra (JEJAK: Jurnal Ekonomi dan Kebijakan, 2009)
The implementation of regional autonomy requires local governments explore the economic potentialexisting in the region to be able to complete with other regions. One of the implications is of centralgovernment being reduced in managing development. Therefore, local revenues have to be found, sothat development can be continously financed. One of the strategies that have to be done by the localgovernment is to stimulate economic sectors, that are potential to develop and able to complete withother regions in Central Java, as source of local development funding. This research will analyze theeconomic potential of the region Boyolali, Karanganyar and Sragen with an analysis of internal andexternal potential. From the analysis of economic sectors that have the potential competitivenesscomparative and competitive superior to the growth of economic activity total for the three areas isagriculture.Keywords: GDP, Sector, Internal Potential, External Potential